Enhancing Pediatric Interns’ Clinical Skills Through Simulation-Based Training - Ba H; Xu L; Peng H; Gu Y; Li Y; Jiang X; Li X; Li S (Advances in Medical Education and Practice, 2025)
Hongjun Ba,* Lingling Xu,* Huimin Peng, Yufen Gu, Yijuan Li, Xiaoyun Jiang, Xiaoyu Li, Shujuan Li Pediatric Department, The First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, 510080, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoyu Li, Email lixiaoyu@mail.sysu.edu.cn Shujuan Li, Email lishuj2@mail.sysu.edu.cnBackground: Situational simulation teaching enhances students’ practical skills and clinical decision-making by replicating real-world scenarios. Pediatric practice often involves complex, dynamic situations, making it crucial for students to gain experience in a controlled environment where repeated practice can develop clinical expertise.Objective: This study aims to evaluate the effectiveness of situational simulation in pediatric clinical practice by comparing its impact on trainees’ skills with that of conventional teaching methods.Methods: A total of 52 pediatric trainees were randomly assigned to two groups: one participating in situational simulation training and the other receiving traditional instruction over a six-week period. A mixed-method approach, including formal assessments and Mini-Clinical Evaluation Exercises (Mini-CEX), was used to assess knowledge, clinical abilities, and overall competencies. A feedback survey was also administered to the simulation group to evaluate the impact of simulation-based training on their learning outcomes.Results: Theoretical exam performance was comparable between both groups, with no significant difference (p > 0.05). However, the situational simulation group showed significant improvements in key skills compared to the traditional group: medical history taking (26.92% vs 69.23%, p = 0.005), clinical judgment (19.23% vs 46.15%, p = 0.011), doctor-patient communication (26.92% vs 61.54%, p = 0.025), and overall clinical competence (19.23% vs 57.69%, p = 0.009). The simulation group also reported higher satisfaction and demonstrated superior competency in practical assessments.Conclusion: This study confirms that situational simulation effectively improves pediatric clinical skills, especially in practical competence and patient communication. The findings support further integration of simulation-based teaching into pediatric training programs to enhance clinical readiness and confidence.Keywords: situational simulation teaching, pediatric clinical training, medical competencies, medical training, mini-clinical assessment